Banana bunchy top virus (BBTV) resistance in cultivar ‘Lakatan’ developed via gamma irradiation of shoot tips (2006)
Banana bunchy top virus (BBTV) is the most destructive virus disease of banana in the Philippines. Incorporation of resistance to this virus disease by conventional hybridization is not possible due to sterility of most commercial banana cultivars. Instead, gamma radiation coupled with in vitro technology was explored as a means to develop BBTV resistance. The sensitivity of banana shoot cultures to Cobalt 60 gamma radiation was determined. Irradiated shoot cultures were micropropagated for 3 to 5 cycles and plants regenerated were potted out and evaluated. Plants were indexed for BBTV using symptomatology, ELISA and PCR techniques. A total of 6,012 plants regenerated from irradiated shoot cultures were subjected to artificial BBTV inoculation using the aphid vector Pentalonia nigronervosa. From these plants, 64 putative BBTV resistant lines were selected in the field after 36 months. The selections exhibited varying degrees of resistance, with 26 lines showing no BBTV symptom expression in both irradiated and first-generation sucker plants. The other 38 lines selected exhibited limited symptom expression. Yield and agronomic characteristics of some resistant lines were comparable to non irradiated micropropagated plants. Suckers from these resistant lines were collected; micropropagated and plants are now being evaluated for the second cycle stability of BBTV resistance trait.
Keywords: Banana bunchy top disease; Banana diseases and pests